THE MULTIPLICATIVE EFFECT OF TOURISM AND ITS IMPACT ON THE DEVELOPMENT OF OTHER INDUSTRIES - MIRZAKHANOVA SADIYA ZAMIRBEKOVNA (TADQIQOTLAR, 2025)
ANNOTATION This  article  discusses  the  concept  of  tourism,  its  theoretical  foundations,  the multiplicative effect of tourism, and its influence on the development of other sectors. It elaborates on the interconnection of the multiplicative effect with economic, social, and ecological factors, as well as the types of economic effects. The main differences between the concepts of direct and indirect effects are explained. Additionally, the article  clarifies  the  concept  of  the  multiplier.  It  discusses  how  to  generate  income through tourism, create job opportunities for the population, and how to allocate tourist expenditures. The article concludes with the significance of the multiplicative effect in enhancing  the  competitiveness  of  hotels.  This  scientific  work  may  be  useful  for practitioners and researchers in the field of economics.